What does expert opinion in guidelines mean? a meta-epidemiological study. Issue 5 (18th September 2017) - Ponce, Oscar J; Alvarez-Villalobos, Neri; Shah, Raj; Mohammed, Khaled; Morgan, Rebecca L; Sultan, Shahnaz; Falck-Ytter, Yngve; Prokop, Larry J; Dahm, Philipp; Mustafa, Reem A; Murad, Mohammad H
Abstract : Guidelines often use the term expert opinion (EO) to qualify recommendations. We sought to identify the rationale and evidence type in EO recommendations. We searched multiple databases and websites for contemporary guidelines published in the last decade that used the term EO. We identified 1106 references, of which 69 guidelines were included (2390 recommendations, of which 907 were qualified as EO). A rationale for using EO designation was not provided in most (91%) recommendations. The most commonly cited evidence type was extrapolated from studies that did not answer guideline question (40% from randomised trials, 38% from observational studies and 2% from case reports or series). Evidence extrapolated from populations that were different from those addressed in the guideline was found in 2.5% of EO recommendations. We judged 5.6% of EO recommendations as ones that could have been potentially labelled as good practice statements. None of the EO recommendations were explicitly described as being solely dependent on the clinical experience of the panel. The use of EO as a level of evidence in guidelines remains common. A rationale for such use is not explicitly provided in most instances. Most of the time, evidence labelled as EO was indirect evidence and occasionally was very low-quality evidence derived from case series. We posit that the explicit description of evidence type, as opposed to using the label EO, may add clarity and transparency and may ultimately improve uptake of recommendations.